Els canvis socioambientals al Pirineu català. La Vall Fosca com a escenari representatiu de les mutacions en les economies tradicionals de muntanya - Jiménez, Maria Barrachina; Tulla Pujol, Antoni Francesc (Documents d’Anàlisi Geogràfica, 2011)
Two opposite processes usually coexist in Pyrenean valleys, as exemplified by the case of Vall Fosca (Pallars Jussà): land abandonment and land use intensification. The first is due to a dramatic decrease in primary activities which made up the basis of a system which would start to disappear as soon as capitalist principles spread out. The second arises from the proliferation of leisure and sports complexes together with urbanisation and fulfills the demands of population coming from urban areas. Extensive mountain stockbreeding, in critical recession today, claims for its role in economic diversification of Pyrenean regions: it would suit perfectly to the territory’s possibilities and would be responsible of landscape quality, which is what tourists demand.